Evaluating the Effects of Reduced N Application, a Nitrification Inhibitor, and Straw Incorporation on Fertilizer-N Fates in the Maize Growing Season: A Field 15N Tracer Study - Zhi Quan; Shanlong Li; Zhifeng Xun; Chang Liu; Dong Liu; Yanzhi Wang; Xinghan Zhao; Ming Yang; Caiyan Lu; Xin Chen; Yunting Fang (Nitrogen)
Reducing fertilizer-N rate, applying a nitrification inhibitor (NI), and incorporating straw are widely recommended to improve N use efficiency of crops and decrease N losses. A field 15N tracer study was conducted to compare their effectiveness on fertilizer-N fates during the maize growing season in Northeast China. The following six treatments were used: (1) no N fertilization (control); (2) 200 kg urea-N ha−1 (100%N); (3) 200 kg urea-N ha−1 and straw (100%N + S); (4) 160 kg urea-N ha−1 (80%N); (5) 160 kg urea-N ha−1 and NI (Nitrapyrin in this study) (80%N + NI); and (6) 160 kg urea-N ha−1, NI, and straw (80%N + NI + S). The results showed that the five N fertilization treatments yielded 16–25% more grain and 39–60% more crop N uptake than the control, but the differences among the five treatments were not statistically significant. Compared with the 100%N, 20% fertilizer-N reduction (80%N) decreased the 15N concentration in topsoil and plant pools but increased the proportion of plant 15N recovery at harvesting (NUE15N, 60% vs. 50%). Compared with the 80%N, NI co-application (80%N + NI) delayed soil nitrification and increased soil 15N retention at harvesting (52% vs. 36%), thereby decreasing NUE15N significantly. Straw incorporation decreased fertilizer-N retention in soil compared with NI co-application because it promoted NUE15N significantly. In conclusion, the results demonstrate that NI and straw additions are efficient strategies for stabilizing fertilizer-N in soils and potentially minimizing N loss; however, their effects on NUE15N vary and the related mechanism must be further clarified in long-term trials.